Fashion segment and industry 4.0: Brazilian textile and clothing industry – Perspective into the new industrial paradigms - Pereira das Neves, E. [UNESP]; Nogueira da Silva, D. [UNESP]; Paschoarelli, L. C.; Moreira da Silva, F. (My University, 2019)
The Brazilian textile and clothing industry have featured in global scenario, not only for being amongst the five biggest industrial complexes of the segment, but also because of their professionalism and creativity. The sector in the last years, although slow and timid, reveals a set of issues that challenges the adequacy of the industrial segment within the Industry 4.0 reality. This paper aims to analyze and summarize the economic reality and the challenges faced by the textile and clothing industry, and the perspectives of investments regarding their adaptation to the new industrial paradigms. It was observed that the Brazilian fashion industry is late regarding the adoption of new technologies, mainly because of financial difficulties and the lack of government support. However, this industry needs to promote itself by adapting to alternative models of smart manufacturing, bridging the gap between supply chain and consumers.